2018
DOI: 10.1109/tbme.2017.2693157
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based Affect and Workload Recognition in a Virtual Driving Environment for ASD Intervention

Abstract: objective To build group-level classification models capable of recognizing affective states and mental workload of individuals with autism spectrum disorder (ASD) during driving skill training. Methods Twenty adolescents with ASD participated in a six-session virtual reality driving simulator based experiment, during which their electroencephalogram (EEG) data were recorded alongside driving events and a therapist’s rating of their affective states and mental workload. Five feature generation approaches inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 37 publications
2
55
1
2
Order By: Relevance
“…It is shown the average performance of the proposed method is competitive against our previous one. Such MW recognition accuracy is also comparable with the newest work reported in [32] , where 0.86 workload classification rate is achieved (note that the environment for implementing classifier is different in two works). However, the subjectspecific classification paradigm is used in [11] while we trained subject-generic classifiers for TDAE.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It is shown the average performance of the proposed method is competitive against our previous one. Such MW recognition accuracy is also comparable with the newest work reported in [32] , where 0.86 workload classification rate is achieved (note that the environment for implementing classifier is different in two works). However, the subjectspecific classification paradigm is used in [11] while we trained subject-generic classifiers for TDAE.…”
Section: Discussionsupporting
confidence: 79%
“…Guler and Ubeyli fused the discrete wavelet transformation and the adaptive neuron fuzzy inference system as a multiclass EEG classifier [31] . In a newly reported work [32] , the classical k -nearest neighbor method also showed high performance. In our previous works [16,33] , we applied the least square support vector machine (LSSVM) and the locally linear embedding to classify operator MW.…”
Section: Related Workmentioning
confidence: 93%
“…Despite these interesting results, our study has several limitations, such as the small sample size; use of nonparametric statistical methods; and the fact that we did not record other physiological parameters of interest, such as respiratory rate and electroencephalography. 50 In addition, it is known that more realistic forms of VR can elicit more intense experiences of awe. Towards this end, we intend to improve the software and apparatus used in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The EEG signals were rerecorded to study the MWs of the crew members during cooperative tasks [19]. Based on EEG data and therapist's evaluation during driving skill training, Fan et al established a group-level classification model to distinguish the emotional states and MW of patients in the autism spectrum disorder during driving skill training [20]. Chen et al demonstrated the validity of EEG signals in evaluating the MW of construction workers and described the development of a wearable EEG safety helmet prototype [21].…”
Section: Related Workmentioning
confidence: 99%